Penggunaan Infografis Pada Media Sosial Kanwil Kemenkumham SUMSEL Dalam Meningkatkan Pemahaman Informasi Publik - Wulandari (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2023)
This research is about the use of infographics as a communication medium in conveying information, which is related to the activities of the Regional Office of the Ministry of Law and Human Rights of South Sumatra. Information is disseminated through social media such as Instagram, Youtube and Tiktok of the Regional Office of the Ministry of Law and Human Rights of South Sumatra. This study uses a case study method with a qualitative approach. This research uses the concept of media theory. The sample in this study were two people using purposive sampling technique. The results of this study are that the Regional Office of the Ministry of Law and Human Rights of South Sumatra has taken the right step in choosing infographics as a medium in delivering information, to attract attention while making it easier for people to understand the content of the message. However, there are still some aspects that must be improved in order to maximize public understanding.